Ghrelin and orotic acid increased in subclinical mastitis - Karatas, F.; Aydin, S.; Kaygusuzoglu, E.; Yildiz, H.; Erulas, F.A.; Ozkan, Y. (My University, 2008)
Hormone ghrelin and orotic acid accelerate wound healing as well as controlling inflammation and immunity. We have, therefore, investigated the serum and milk levels of ghrelin and orotic acid in dairy cows with (n = 21) or without (n = 21) subclinical mastitis. Acylated and des-acylated ghrelin as well as orotic acid concentration were detected by using high performance liquid chromatography (HPLC). The results revealed that ghrelin level in milk and serum was significantly higher in dairy cows with subclinical mastitis than that of dairy cows without subclinical mastitis. This was also the case when the orotic acid concentrations in dairy cows with subclinical mastitis were compared with those dairy cows without subclinical mastitis. In conclusion, ghrelin and orotic acid occur in particularly high concentrations in subclinical mastitis, and might, therefore, be required in greater amounts for tissue repair and may be also used as a indicator for subclinical mastitis. © 2008 Informa UK Ltd.
Keywords: Cow milk; Ghrelin; Orotic acid; Subclinical mastitis